Removal of Chloridazon and Its Metabolites from Soil and Soil Washing Water by Electrochemical Processes - Salazar-Gonzalez, R; Calzadilla-Aguiar, W; Calzadilla-Aguiar, W (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
This work deals with the electro-remediation of two soils enriched with chloridazon (CLZ), an herbicide widely used in agriculture for the main control of beets and corn. It is considered relatively harmless, but its main metabolites, desphenyl-chloridazon (DPC) and methyl-desphenyl-chloridazon (Me-DPC), can be a threat to surface and groundwater resources. The electro-kinetic soil washing (EKSW) process was studied by applying direct (DP) and alternate polarity (AP) during 15 days with an electric field of 1 V cm(-1) between the electrodes. The removal percentage for a clay soil was 100% and 63%, respectively. Considering that EKSW-AP did not modify the physicochemical properties of the soil, it was applied to a soil with a high organic matter, reaching 51% elimination. The retention capacity of CLZ was tested in both soils using mobility tests in columns. The washing water from the EKSW-AP process was treated by electro-oxidation in order to assess the effect of current density on the degradation of CLZ, Me-DPC, and DPC. The generation of center dot OH on the surface of the anode allowed a complete degradation and partial mineralization of these pollutants. The kapp for the pseudo-first order degradation of CLZ, Me-DPC, and DPC were 0.0359, 0.0329, and 0.0220 min-1, respectively. Likewise, 6 aromatic by-products were identified during electro-oxidation, and the evolution of 4 carboxylic acids and 3 inorganic ions was followed. The results showed that the application of both coupled stages would allow the removal of CLZ from the soil and the washing water.